Engaging Stem Cells for Customized Tendon Regeneration. (16th May 2012) - Thaker, Hatim; Sharma, Arun K.
Abstract : The need for a consistent therapeutic approach to tendon injury repair is long overdue. Patients with tendon microtears or full ruptures are eligible for a wide range of invasive and non invasive interventions, often subjectively decided by the physician. Surgery produces the best outcomes, and while studies have been conducted to optimize graft constructs and to track outcomes, the data from these studies have been inconclusive on the whole. What has been established is a clear understanding of healthy tendon architecture and the inherent process of healing. With this knowledge, tissue regeneration efforts have achieved immense progress in scaffold design, cell line selection, and, more recently, the appropriate use of cytokines and growth factors. This paper evaluates the plasticity of bone-marrow-derived stem cells and the elasticity of recently developed biomaterials towards tendon regeneration efforts. Mesenchymal stem cells (MSCs), hematopoietic progenitor cells, and poly(1, 8-octanediol co-citrate) scaffolds (POC) are discussed in the context of established grafting strategies. With POC scaffolds to cradle the growth of MSCs and hematopoietic progenitor cells, developing a fibroelastic network guided by cytokines and growth factors may contribute towards consistent graft constructs, enhanced functionality, and better patient outcomes.